2012
DOI: 10.1089/apc.2012.0048
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2 Encephalitis: Case Report and Literature Review

Abstract: We report the case of a 59-year-old man who moved from Cape Verde to Massachusetts at the age of 29. He had multiple sexual contacts with female partners in Cape Verde and with West African women in Massachusetts, as well as multiple past indeterminate HIV-1 antibody tests. He presented to our facility with 2-3 months of inappropriate behaviors, memory impairment, weight loss, and night sweats, at which time he was found to have an abnormal enhancing lesion of the corpus collosum on brain magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Like HIV‐1, HIV‐2 is neurotropic with demonstrable CNS infection . Neurological syndromes in HIV‐1 and HIV‐2 infection show considerable overlap, including conditions that may be inflammatory, such as demyelinating diseases , and those considered due to direct CNS infection, such as encephalitis . An early autopsy study suggested that encephalitis may be more frequent in HIV‐2 than in HIV‐1 , which may be related to the broader range of co‐receptors available for HIV‐2 .…”
Section: Lessons From the Clinic—how Do Clinical Manifestations Diffementioning
confidence: 99%
“…Like HIV‐1, HIV‐2 is neurotropic with demonstrable CNS infection . Neurological syndromes in HIV‐1 and HIV‐2 infection show considerable overlap, including conditions that may be inflammatory, such as demyelinating diseases , and those considered due to direct CNS infection, such as encephalitis . An early autopsy study suggested that encephalitis may be more frequent in HIV‐2 than in HIV‐1 , which may be related to the broader range of co‐receptors available for HIV‐2 .…”
Section: Lessons From the Clinic—how Do Clinical Manifestations Diffementioning
confidence: 99%
“…3 HIV encephalitis has been documented in HIV-2 cases not on ART or failing on ART. 4,5 However, hardly anything is known about progressive neurologic disease in otherwise well-controlled HIV-2 infection.…”
Section: Introductionmentioning
confidence: 99%